2000
DOI: 10.1007/s007020070054
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the synaptic protein rab3a in the thalamus and connecting brain regions in post-mortem schizophrenic brains

Abstract: Although the psychotic symptoms in schizophrenia can be alleviated by treatment with dopaminergic receptor antagonists, the etiology and underlying neurochemical pathology remains obscure. Both neuropathological and magnetic resonance imaging studies have found evidence for neuronal loss and atrophy in the thalamus in schizophrenia, implicating this key structure for gating information to cortical areas in the pathophysiology. Recent studies have also found evidence of synaptic loss in the thalamus in schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
1
8
0
2
Order By: Relevance
“…Other studies have reported schizophrenia-related reductions in volume and/or neuronal number in the thalamic nuclei highlighted by our techniques [11]- [16]. Altered glutamatergic NMDA receptor expression [17] and synaptic dysfunction or loss [18] have also been detected in the anterior and mediodorsal thalamic nuclei in patients with schizophrenia. Most importantly, our findings support and extend the results of previous spectroscopic investigations with voxels localized to the mediodorsal and anterior regions of the thalamus [26]- [28].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Other studies have reported schizophrenia-related reductions in volume and/or neuronal number in the thalamic nuclei highlighted by our techniques [11]- [16]. Altered glutamatergic NMDA receptor expression [17] and synaptic dysfunction or loss [18] have also been detected in the anterior and mediodorsal thalamic nuclei in patients with schizophrenia. Most importantly, our findings support and extend the results of previous spectroscopic investigations with voxels localized to the mediodorsal and anterior regions of the thalamus [26]- [28].…”
Section: Discussionsupporting
confidence: 57%
“…Neuroimaging studies have demonstrated somewhat inconsistent thalamic alterations in schizophrenia, including changes in thalamic volume [3] and connectivity [4] as shown by MRI; abnormalities in glucose metabolism in the mediodorsal, anterior, and pulvinar regions of the thalamus as measured by blood-oxygen-level-dependent (BOLD) functional magnetic resonance imaging (fMRI) [5]- [9]; differences in thalamic mean diffusivity as revealed by MRI diffusion tensor imaging [10]; reductions in volume and/or neuronal number in the mediodorsal nucleus and pulvinar [11]- [16]; and altered glutamatergic N-methyl-D-aspartic acid (NMDA) receptor expression [17] and synaptic dysfunction or loss [18] in the anterior and mediodorsal thalamic nuclei in patients with schizophrenia. In our work, we wanted to generate in vivo experiments to explore the relationship between different nuclei in the thalamus and schizophrenia.…”
Section: A Neuroimaging Studies Of the Thalamusmentioning
confidence: 99%
“…120 BDNF administration can also increase the expression of some presynaptic terminal proteins, most notably Rab3a, 121 which is reportedly decreased in the thalamus of patients with schizophrenia. 122 Further, the number of thalamic neurons in the medial dorsal nuclei, which send excitatory projections to the DLPFC, may be reduced in patients with schizophrenia. [123][124][125][126][127] The reduction in thalamic neuronal number in schizophrenia could be caused by a reduction in cortically derived BDNF levels in schizophrenia, as neurons in the thalamus are dependent on BDNF for their survival.…”
Section: Potential Consequences Of Reduced Bdnfmentioning
confidence: 99%
“…[45] eine signifikante bilaterale Reduktion des Rab3a-Proteins als einen Marker für die Synapsenzahl in der Schizophreniegruppe gegenüber einer normalen Vergleichsgruppe. Aus der gleichen Arbeitsgruppe wurde in einer weiteren Post-mortem-Studie [46] über eine Reduktion von Synaptophysin im linken Thalamus bei Schizophrenie-Patienten gegenüber einer normalen Vergleichsgruppe berichtet, was insgesamt auf eine gestörte synaptische Funktion im Thalamus in der Schizophreniegruppe hinweist.…”
Section: Introductionunclassified
“…In keiner der Arbeiten, die Neuroleptika-behandelte Patienten untersucht haben, ergaben sich signifikante Assoziationen zwischen der Dauer der Erkrankung, bzw. kumulativer Neuroleptika-Dosis und den festgestellten morphologischen Veränderun-gen [31,36,37,39,40,45,47]. Daher erscheint die Annahme wenig plausibel, dass die beschriebenen pathologischen Post-mortem-Befunde im Thalamus hauptsächlich auf die Einnahme von Neuroleptika zurückzuführen seien.…”
Section: Introductionunclassified